Android-Based Applications for Children's Leaf Recognition Learning - Teguh Hardianto Putra; Ade Eviyanti (Procedia of Engineering and Life Science, 2021)
Indosesia is a country with abundant natural wealth. Almost all types of plants can be grown in the territory of Indonesia. Most have been used in the past to treat various diseases. Therefore, the author wants to design and build a leaf recognition learning application in android-based children that aims to make the younger generation know the diversity of plant leaves in the surrounding environment, in order to make the younger generation understand the need to care for and maintain the natural environment and knowledge about plants that are very important for human life, especially for human health, among others, traditional medicine that is now beginning to fade. This application has ease of use because it has an easy to understand design and a menu that is easy to understand by all people in accessing this application. In this study the author used waterfall method as the process or flow of the research to be done. The test results of the application that has been created get the result that all features and functions of the system can run according to what has been designed. In addition, the author also conducted tests using the UAT method to get a result of a percentage value of 96% so that it can be concluded that this application can be accepted by users.